Translational repression of thymidylate synthase by targeting its mRNA - Garg, Divita; Beribisky, Alexander V.; Ponterini, Glauco; Ligabue, Alessio; Marverti, Gaetano; Martello, Andrea; Costi, M. Paola; Sattler, Michael; Wade, Rebecca C. (Nucleic acids research, 2013)
Resistance to drugs targeting human thymidylate synthase (TS) poses a major challenge in the field of anti-cancer therapeutics. Overexpression of the TS protein has been implicated as one of the factors leading to the development of resistance. Therefore, repressing translation by targeting the TS mRNA could help to overcome this problem. In this study, we report that the compound Hoechst 33258 (HT) can reduce cellular TS protein levels without altering TS mRNA levels, suggesting that it modulates TS expression at the translation level. We have combined nuclear magnetic resonance, UV-visible and fluorescence spectroscopy methods with docking and molecular dynamics simulations to study the interaction of HT with a region in the TS mRNA. The interaction predominantly involves intercalation of HT at a CC mismatch in the region near the translational initiation site. Our results support the use of HT-like compounds to guide the design of therapeutic agents targeting TS mRNA.
Gesehen am 27.01.2020